2020
DOI: 10.1016/j.heliyon.2020.e04780
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-131 labeled genistein as a potential radiotracer for breast cancer

Abstract: Genistein is an isoflavone compound that has been proven to have anticancer activity and is capable of binding to estrogen β receptors with Selective Estrogen Receptor Modulators (SERMs) properties, and has a strong affinity to inhibit the development of cancer cells. This study is to determine the optimum conditions of the reaction in the synthesis process of compounds labeled 131 I-genestein which can be potential for application of breast cancer diagnosis. Methods: Synthesis of 131 I-Genistein compound labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…At present, surgery is the mainstay of treatment for thyroid cancer. Due to the slow progression of thyroid cancer and the low degree of malignancy, it has been reported that palliative treatment with thyroid hormones after tumor resection could achieve favorable results [ 16 ]. However, prior research has shown that most recurrence and metastasis occur within 5 years after surgery [ 17 , 18 ], which was similar to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…At present, surgery is the mainstay of treatment for thyroid cancer. Due to the slow progression of thyroid cancer and the low degree of malignancy, it has been reported that palliative treatment with thyroid hormones after tumor resection could achieve favorable results [ 16 ]. However, prior research has shown that most recurrence and metastasis occur within 5 years after surgery [ 17 , 18 ], which was similar to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The application of radioimmunoconjugates (RICs) in the brachytherapy of malignant tumors by vascular intervention or by direct implantation has achieved remarkable success, over the past 25 years, a wide variety of RICs labeled with radioisotopes (i.e., 111 In, 89 Zr and 131 I) have been explored and translated to the clinic [ 6 8 ]. Among the numerous radionuclides used in diagnosis and therapy, iodine-131 ( 131 I) is a rare radioisotope with both γ- and β-particle emission characteristics; it has a half-life of 8.1 days and is routinely commonly used in radionuclide labeling [ 9 ]. Moreover, free 131 I that dissociates from a RICs accumulates in the thyroid gland or is excreted, but is not excreted from the body but accumulates in the liver, spleen, and bone, which has almost no side effects [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…RT has been considered an immunosuppressive treatment, and it has been extensively reported to have immunomodulatory effects in preclinical and clinical studies [ 2 , 20 ]. RT releases tumor-specific antigens and activates the immune signaling pathway [ 21 ], accelerates programmed cell death by immune mediation [ 22 ], modulates the TME, increases immunocyte infiltration in tumors [ 23 ], stimulates tumor-specific cytotoxic T cells, and enhances T cell homing, engraftment and function in tumors [ 9 , 24 ]. Therefore, the synergistic effect of RT and immunotherapy is well known.…”
Section: Introductionmentioning
confidence: 99%